1982
DOI: 10.1002/tera.1420260205
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of chlorambucil in rat embryos in vitro

Abstract: Chlorambucil, a bifunctional alkylating agent and antitumor drug, is a potent teratogen in rodents and possibly teratogenic in humans. Unlike cyclophosphamide, a related bifunctional alkylating agent, chlorambucil is a direct-acting cytotoxic agent. However, several studies indicate that the cytotoxic potential of chlorambucil is enhanced by metabolism of the parent compound. Using day-10 rat embryos cultured in vitro, we have demonstrated that chlorambucil is a direct acting teratogen but that its teratogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Most workers have found at least reasonable correspondence between the two sets of curves, but there are clear exceptions. We have found good correspondence for cyclophosphamide [14,16} and chlorambucil [16,26]. By contrast, we have been unable to detect clear evidence of teratogenicity with thalidomide.…”
Section: Val I D At I 0 Nmentioning
confidence: 83%
See 1 more Smart Citation
“…Most workers have found at least reasonable correspondence between the two sets of curves, but there are clear exceptions. We have found good correspondence for cyclophosphamide [14,16} and chlorambucil [16,26]. By contrast, we have been unable to detect clear evidence of teratogenicity with thalidomide.…”
Section: Val I D At I 0 Nmentioning
confidence: 83%
“…We and a number of other workers have found that extraembryonic (maternal) metabolism, but not fetal metabolism is instrumental in the teratogenicity of a number of compounds. These compounds include cyclophosphamide [ 14,22,23], cytochalasin D [24], N-2-fluorenylacetamide [25], chlorambucil [26], rifampicin [27], and procarbazine (Fantel, unpublished data). These findings are consistent with the inability of a number of workers to detect significant cytochrome P-450-dependent activity in embryos [28-321. Other studies have shown that as for many mutagens and carcinogens, inducing agents and metabolic inhibitors are effective modifiers of teratogenicity [ 1 5,221.…”
Section: Metabolism Of Teratogensmentioning
confidence: 99%
“…The second involves isolating rat liver supernatants (S-9) or microsomes and adding them, together with the cofactor NADPH, to embryo cultures. Results show that these activating systems do not impede or alter normal development in culture and are capable of initiating both activation and inactivation of teratogens (Fantel et at., 1979(Fantel et at., , 1981Kitchin et at., 1981a,b;Mirkes and Greenaway, 1982;Mirkes et at., 1983). Finally there is the potential of monitoring the teratogenicity of sera from animals treated with a potential teratogen, which presumably would contain metabolites, the parent compound, or both (Sadler, 1980b;Klein and Pierro, 1983).…”
Section: Teratogen Screeningmentioning
confidence: 95%
“…Vitamin A (Morriss and Steele, , 1977Davis and Sadler, 1981), hydroxyurea (Warner et at., 1983), cadmium , alcohol (Brown et at., 1979), valproic acid and diphenylhydantoin (Bruckner et a!., 1983), glucose (Cockroft and Coppola, 1977;Sadler, 1980a), increased O 2 (Morriss and New, 1979), chlorambucil (Mirkes and Greenaway, 1982), cyclophosphamide (Fantel et at." 1979;Mirkes et at., 1983), and hyperthermia New, 1975, 1978) have caused abnormalities in growth and development.…”
Section: Direct Addition Of Teratogensmentioning
confidence: 96%
“…It was shown with murine sarcoma cells that PAM (2) has a stronger acute toxicity and antitumor activity than CLB (1) [20]. Similarly, 2 was more cytotoxic and also more teratogenic than 1 in a rat-embryo model [21].…”
Section: '-Deoxy-5-methylcytidinementioning
confidence: 97%